HMGB1-mediated DNA bending: Distinct roles in increasing p53 binding to DNA and the transactivation of p53-responsive gene promoters - Štros, Michal; Kučírek, Martin; Sani, Soodabeh Abbasi; Polanská, Eva (Biochimica et biophysica acta. Gene regulatory mechanisms, 2018)
HMGB1 is a chromatin-associated protein that has been implicated in many important biological processes such as transcription, recombination, DNA repair, and genome stability. These functions include the enhancement of binding of a number of transcription factors, including the tumor suppressor protein p53, to their specific DNA-binding sites. HMGB1 is composed of two highly conserved HMG boxes, linked to an intrinsically disordered acidic C-terminal tail. Previous reports have suggested that the ability of HMGB1 to bend DNA may explain the in vitro HMGB1-mediated increase in sequence-specific DNA binding by p53. The aim of this study was to reinvestigate the importance of HMGB1-induced DNA bending in relationship to the ability of the protein to promote the specific binding of p53 to short DNA duplexes in vitro, and to transactivate two major p53-regulated human genes: Mdm2 and p21/WAF1. Using a number of HMGB1 mutants, we report that the HMGB1-mediated increase in sequence-specific p53 binding to DNA duplexes in vitro depends very little on HMGB1-mediated DNA bending. The presence of the acidic C-terminal tail of HMGB1 and/or the oxidation of the protein can reduce the HMGB1-mediated p53 binding. Interestingly, the induction of transactivation of p53-responsive gene promoters by HMGB1 requires both the ability of the protein to bend DNA and the acidic C-terminal tail, and is promoter-specific. We propose that the efficient transactivation of p53-responsive gene promoters by HMGB1 depends on complex events, rather than solely on the promotion of p53 binding to its DNA cognate sites.
Keywords: nádorový supresorový protein p53; Mutant Proteins; DNA-protein interaction; Transcriptional Activation; nádorové buněčné linie; konformace nukleové kyseliny; protein HMGB1; Nucleic Acid Conformation; Cyclin-Dependent Kinase Inhibitor p21; Protein Binding; DNA; HMGB; Promoter Regions, Genetic; DNA bending; HMGB1 Protein; mutace; protoonkogenní proteiny c-mdm2; Tumor Suppressor Protein p53; Cell Line, Tumor; Oxidation-Reduction; Proto-Oncogene Proteins c-mdm2; Protein Domains; p53; Mutation; Humans; inhibitor p21 cyklin-dependentní kinasy; aktivace transkripce; vazba proteinů; promotorové oblasti (genetika); oxidace-redukce; Promoter transactivation; mutantní proteiny; proteinové domény; lidé